405 - Music Therapy in the management of dementia. (October 2020) - Pedro, Catarina; Jorge, Beatriz; Duarte, Mariana
Abstract : Introduction: Dementia has become a worldwide concern. According to the World Health Organization, there are 50 million individuals suffering from dementia across the world and approximately 20 million new cases are diagnosed each year. The efficacy of medications in controlling agitation and psychotic symptoms is modest and may cause serious adverse effects, outlining the urge for new treatment methods for patients with dementia. Music therapy (MT) is a nonpharmacologic strategy that is used in patients with early-to-late stages of dementia with promising results. Objectives: The aim of this presentation is to evaluate the benefits of music therapy in cognitive functioning and neuropsychiatric symptoms in patients diagnosed with dementia. We also summarize the current knowledge about this topic. Methods: A non-systematic review of the literature was performed on PubMed, PsycINFO and Web of science using selected keywords. Results: MT sustains its benefit because musical memory regions in the brain are relatively spared compared to cognitive function. "Musical memories" can, thus, be stored longer than non-musical memories, allowing to recall associated life events and emotions. Systematic reviews suggest that MT seem to have a positive effect on symptoms such as depression, anxiety and behavioral problems while the findings concerning agitation/aggression are inconsistent. No large differences were found between studies using live or recorded music although the latter reported more of a consistently positive impact on behavioral and psychological outcomes. The studies using live music, however, reported specific benefits to relationships and interactions. Conclusions: The majority of the studies have methodological limitations, making it difficult to offer firm conclusions. Despite this, there were positive results on aspects of quality of life, cognitive function, behavioral, psychological, physiological and communication outcomes.